Redefining toys, games and entertainment products by teaching about playful interactions. (21st December 2009) - Bekker, Tilde; Hummels, Caroline; Nemeth, Sam; Mendels, Philip
This paper describes how students are taught to design (computer) games and toys in a broad sense of the word at the Department of Industrial Design at the Eindhoven University of Technology. The curriculum is highly project driven, which means that students acquire a large amount of hands-on experience during concrete projects. One major theme within the department is the design of playful interactions, which focuses on the design of innovative concepts that support expressing oneself and exploration. In this theme, we design for opportunities and exploration instead of goal-oriented products. Our educational approach is illustrated with examples both from an assignment on game design and design projects on playful interaction.